2012
DOI: 10.1159/000339631
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Disease Caused by Rapidly Growing Mycobacteria: A Retrospective Study of 44 Cases in Japan

Abstract: Background: The features of pulmonary disease caused by rapidly growing mycobacteria (RGM) have not been sufficiently documented. Objectives: To establish these features, we retrospectively evaluated 44 patients. Methods: We screened respiratory isolates at the National Toneyama Hospital (Osaka, Japan) between 2003 and 2007. Diagnosis was based on the latest guidelines of the American Thoracic Society. The patients were classified into 3 types according to their radiographic findings: fibrocavitary, nodular br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Furthermore, we identified M. abscessus to be the most important RGM in our setting across all specimen sites; M. fortuitum group that was reported to be the most common RGM species in the earlier study was implicated in only 22% of our cases. This finding is consistent with reports from Taiwan [8,14,15] and Japan [16], and it underscores the importance of M. abscessus in the epidemiology of RGM infections in Asia. Unfortunately, M. abscessus is resistant to many currently available antibiotics, with amikacin and clarithromycin as the only two agents with reliable in vitro activity.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we identified M. abscessus to be the most important RGM in our setting across all specimen sites; M. fortuitum group that was reported to be the most common RGM species in the earlier study was implicated in only 22% of our cases. This finding is consistent with reports from Taiwan [8,14,15] and Japan [16], and it underscores the importance of M. abscessus in the epidemiology of RGM infections in Asia. Unfortunately, M. abscessus is resistant to many currently available antibiotics, with amikacin and clarithromycin as the only two agents with reliable in vitro activity.…”
Section: Discussionsupporting
confidence: 91%
“…M. fortuitum is included in the rapidly growing group of mycobacteria in which visible colonies can be produced within 7 days, and many clinicians believe that M. fortuitum is not often pathogenic. However, M. fortuitum has been identified as a pathogenic NTM species in several previous studies (29)(30)(31). According to a recent study in a Japanese population, the second-most-common rapidly growing mycobacteria pathogen was M. fortuitum, following M. abscessus (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, M. fortuitum has been identified as a pathogenic NTM species in several previous studies (29)(30)(31). According to a recent study in a Japanese population, the second-most-common rapidly growing mycobacteria pathogen was M. fortuitum, following M. abscessus (31). It has been shown that lung disease caused by M. fortuitum usually occurs in patients with predisposing factors, such as malignancy, renal transplantation, chronic reflux disease, achalasia, bronchiectasis, or cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies from different regions, infections with rapidly growing mycobacteria were less frequently and infections with M. kansasii , M. malmoense , or M. xenopi more frequently associated with fibrocavitary disease [43,44,54,55,58,60,61,62,63,64,65] (fig. 1), demonstrating a species dependency of the different forms of NTM disease.…”
Section: Clinical Presentationmentioning
confidence: 99%